Ceramics as a Medium for Teaching Fine Arts to Elementary School Students in Ã¢â‚¬Å“SDITÃ¢â‚¬Â Permata Hati Banjarnegara - Puspita, Ratna; Rohidi, Tjetjep Rohendi; Triyanto, Triyanto (Universitas Negeri Semarang, 2018)
In the school-based curriculum of fine arts, a school can teach its material to students, including making crafts from ceramics. This research discusses the use of ceramics as a medium for teaching fine arts to elementary school students in Ã¢â‚¬Å“SDITÃ¢â‚¬Â Permata Hati, Banjarnegara. This research employed qualitative design with the interdisciplinary approach. It used observation, interview, and literature reviews to collect the data. The data were validated using triangulation. The research followed the sequence of analysis starting from data reduction, data presentation, and verification. This research found that ceramics, as the medium of teaching fine arts, can initiate ideas and creativity for the children. Then, the teaching of fine arts teaches the students to appreciate and create artworks in SDIT Permata Hati inside and outside of the school in the centre of ceramics artisans.